Synthesis and characterization of copper antimony tin sulphide thin films for solar cell applications - Ali, N. (Elsevier B.V., 2016)
Low price thin film modules based on Copper antimony tin sulphide (CATS) are introduced for solar harvesting to compete for the already developed compound semiconductors. Here, CATS thin films were deposited on soda lime glass by thermal evaporation technique followed by a rapid thermal annealing in an argon atmosphere. From Our XRD analysis, it was revealed that the annealed samples were poly-crystalline and their crystallinity was improved with increasing annealing temperature. The constituent elements and their corresponding chemical states were identified using X-ray photoelectron spectroscopy. The obtained optical band gap of 1.4 eV for CATS thin film is found nearly equal to GaAs – one of the highly efficient thin film material for solar cell technology. Furthermore, our observed good optical absorbance and low transmittance for the annealed CATS thin films in the visible region of light spectrum assured the aptness of the CATS thin films for solar cell applications.